THE EFFICIENCY OF CORPUS LINGUISTIC IN TEACHING GRAMMAR - Barnoeva, Nilufar Yoqubovna (Innovative Development in Educational Activities, 2023)
The development of grammar instruction and research has begun in the past two decades (Conrad, 2000). Teaching English grammar has been delivered via a traditional method. The present study provides a literature review of how grammar instruction has been influenced by corpus linguistic (CL). The review points out the benefits of implementing corpus-based approach in grammar instruction and some difficulties encountered both teachers and students when applying CL tools. The perceptions of students and teachers towards using CL in grammar instruction was also highlighted. Overall, the participants in the reviewed studies reported positive perceptions towards using corpus-based approach in grammar instruction. Implementing this approach helps teachers design suitable materials and students gain grammar knowledge. It is suggested that further studies are needed to investigate the effectiveness of corpus-based approach in specific grammatical aspects.